Green Marketing as a Strategic Choice To Sustain The Competitiveness of The Algerian Economic Establishment (Case Study of Naftal Algeria - GPL Branch) - Benabdelaziz, Soufyane; Idouli, Lakhdar; Benabdelaziz, Samir (Finance and Business Economies Review, 2019)
It has been linked to the concept of green marketing is closely linked to the concept of social responsibility for marketing, and the most important factor contributing to the dissemination of the evolution of this concept, is to increase environmental awareness and concern for the environment, either by the community or business organizations that found itself obliged to concern for the environment, especially in light of the current economic challenges and requirements of integration into the world economic system. Therefore, this study seeks to identify what green marketing, its importance, its dimensions, as well as the elements of marketing mix in green dammed the theoretical side in westerns applied to highlight the reality of green marketing in the institution naftal Algeria's farewell to the findings and recommendations are important.